Microbial diversity in camel milk from Xinjiang, China as revealed by metataxonomic analysis - Sun, Miao; Shao, Wei; Liu, Zhengyu; Ma, Xianlan; Chen, He; Zheng, Nan; Zhao, Yankun (Frontiers in Microbiology, 2024)
The quality of raw camel milk is affected by its bacterial composition and diversity. However, few studies have investigated the bacterial composition and diversity of raw camel milk. In this study, we obtained 20 samples of camel milk during spring and summer in Urumqi and Hami, Xinjiang, China. Single-molecule real-time sequencing technology was used to analyze the bacterial community composition. The results revealed that there were significant seasonal differences in the bacterial composition and diversity of camel milk. Overall, Epilithonimonas was the most abundant bacterial genus in our samples. Through the annotated genes inferred by PICRUSt2 were mapped against KEGG database. Non-parametric analysis of the bacterial community prediction function revealed a strong bacterial interdependence with metabolic pathways (81.83%). There were clear regional and seasonal differences in level 3 metabolic pathways such as fat, vitamins, and amino acids in camel milk. In addition, we identified lactic acid bacteria in camel milk with antibacterial and anti-tumor activities. Our findings revealed that camel milk from Xinjiang had serious risk of contamination by psychrophilic and pathogenic bacteria. Our research established a crucial theoretical foundation for ensuring the quality and safety of camel milk, thereby contributing significantly to the robust growth of China's camel milk industry.